Cultivars Differences in Keeping Quality and Bioactive Constituents - Ilic, Zoran S.; Mirecki, Natasa; Fallik, Elazar (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
The aims of this research were to evaluate the keeping quality (water loss, firmness, decay incidence) and bioactive constituents (vitamin C, antioxidant activity) of three commercial bell pepper cultivars (Selika-red, Dynamo-yellow and Sympathy-orange color) held for 21 days (d) storage at 7 oC and market simulation (3 d at 20 oC). Cultivars type significantly influenced fruit quality in bell pepper after prolonged storage. The low skin wax content (0.6 ngcm-2) and thin pericarp tissue (6.5 mm) in Sympathy appeared to have contributed greatly to the high weight loss (5.2%), resulting in very soft fruits (4 mm), high decay incidence (20%) and lowest value in general appearance (2.5) among to the three cultivars. After 21 d storage at 7 oC plus 3 d at 20 oC content of ascorbic acid showed a insignificant increase in all cultivars. Hydrophilic antioxidant activity (HAA) remains practically unchanged after 3 weeks at 7 oC (between 2 and 5%) from the initial value. Total antioxidant activity (TAA) increases only in red pepper ’Selika’ (6.07 µmol TE/g fr.wt.) and this increase is mainly because of changes in the lipophilic antioxidant activity (LAA - from 0.84 in harvest time increased to 2.31 µmol TE/g fr.wt. after storage).